ASUPAN PROTEIN, VITAMIN A, ZINC, DAN STATUS IMUNISASI PADA STATUS GIZI BALITA DENGAN ISPA - Milla Destania; Tetes Wahyu; Afryana Siregar (Poltekkes Kemenkes Bengkulu, 2020)
Abstract : The purpose of this study was to find out the intake of protein, vitamin A, zinc and status immunization with nutritional status on toddler of acute respiratory infection (ARI) age 12-24 months in Sukamerindu Health Centre Bengkulu City 2017. This research uses cross sectionalapproach with technique of acidental sampling according to inclusion and exclusion criteria of 41 samples. The results showed that pearson correlation test showed that there was a correlation between protein intake with nutritional status (p= 0.0005), there was correlation of zinc with nutrient status (p= 0,013), there was no correlation between vitamin A intake with nutritional status of spearman test (p= 0,075), and there was no relation of immunization status with nutritional status from result of chi-square test (Fisher's Exact Test) got value (p= 1,000). Suggestions for health centre can provide socialization or education about the importance of high intake of protein, vitamin A, and zinc that can boost the immune system to avoid infectious diseases such as ARI.Keywords : Intake Protein, Vitamin A, Zinc, Immunization Status, Nutrional Status ARI